Origins of medical education on the territory of modern Ukraine - Kulichenko, A.; Boichenko, M.; Куліченко, Алла Костянтинівна (My University, 2021)
The article deals with the origins of Ukrainian medical education during two historical periods – the period of Proto-Slavic medicine (6th century BC – 7th century AD) and the period of folk, secular and monastic medicine of the Kyivan Rus (9th – 13th centuries AD). There are the following methods, applied in the research: content analysis and generalization of references, method of historical reconstruction, and cultural and historical method. The period of Proto-Slavic medicine is characterized as the beginning of the activity of healers, fortune-tellers, priests, magicians, midwives, who combined the rational things with the irrational ones. In the period of folk, secular, and monastic medicine of the Kyivan Rus there was a combination of pagan and Byzantine ideas in all spheres of life.
Keywords: development; folk medicine; medical education; monastic medicine; ProtoSlavic medicine; secular medicine; Ukraine